Brand Perception of Kopi Kenangan as Green Economy Brands in Sustainable Business Practices - Deddy Muharman; Marlinda Irwanti (Ikatan Sarjana Komunikasi Indonesia, 2025)
This study aims to analyze consumer perception of Kopi Kenangan as a green economy brand and its impact on loyalty as part of their sustainable business practices. With consumer awareness of sustainability increasing, this study examines how sustainability initiatives such as the use of eco-friendly materials, operational efficiency, and collaboration with local communities affect consumer perceptions. Using a qualitative approach, this study applies document analysis to company reports, media reports, and digital content used by Kopi Kenangan in communicating its sustainability commitments. The goal is to identify communication patterns and brand strategies that shape consumer perception of Kopi Kenangan as a green brand. The results of this research are expected to provide strategic input for startups and other F&B industry players in developing a sustainable and credible brand image in the eyes of consumers.The results of the study are expected to provide strategic insights for Kopi Kenangan to strengthen the brand's green image through a consistent and credible communication strategy, as well as make a theoretical contribution to the literature related to the perception of green brands in Indonesia. This research is also expected to serve as a reference for other brands that want to integrate green economy principles in their business strategies.